PWE-110 Impact of a simulation-based induction programme in gastroscopy on trainee outcomes. (June 2019) - Siau, Keith; Hodson, James; Edwards, Kate; Neville, Peter; Turner, Jeff; Green, Susie; Beale, Amanda; Murugananthan, Aravinth; Dunckley, Paul; Hawkes, Neil D
Abstract : Introduction: Pre-clinical simulation-based training (SBT) in endoscopy is associated with improvements in trainee performance and patient outcomes. However, the durability of trainee benefit is unclear, and pre-clinical SBT remains largely unavailable in the UK. We assessed the impact of a gastroscopy induction programme (SPRINT), a two day course with review of skills handling, lesion recognition, JETS e-portfolio, report writing and a SBT curriculum, on the outcomes of novice endoscopists. Methods: In this prospective case-control study, new ST3 endoscopy trainees from three UK deaneries were enrolled to SPRINT in Sep 2017. Each received expert-led teaching with >3hrs of SBT via the Surgical Science EndoSim platform. Post-course progress of attenders (cases) was compared with controls matched from the JETS training database, with follow-up until Feb 2019. Those with >50 procedures preceding SPRINT were excluded. Outcomes derived from JETS included: 1) unassisted D2 intubation rates, 2) time to 200 procedures, 3) time to JAG certification for independent practice. Comparisons of learning curves (D2 intubation) were made using generalised estimating equations, and of time to each milestone using Kaplan-Meier plots with Cox regression. Results: After exclusions, data from 15 cases and 24 controls were analysed. Prior to the date of SPRINT, the mean lifetime procedure counts were similar in cases and controls (10 vs. 3, P=0.739), with 60% of cases and 63% of controls having no experience. Learning curve analysis found no significant difference in the rate of improvement by procedure count between the groups (p=0.205), with D2 intubation rates of 82% vs. 78% in cases vs. controls by the 50th post-SPRINT procedure. Over the 16-month follow up period, 87% of cases and 63% of controls reached their 200th procedure. The Kaplan-Meier estimated time to 200 procedures (Figure 1A ) did not differ significantly between cases and controls (10.6 vs. 12.1 months; P=0.190). Cases performed a median of 16.2 procedures per month post-SPRINT vs. 13.8 in the control group (P=0.051). JAG certification was achieved in 73% of cases and 29% of controls. The median time to certification (Figure 1B ) was earlier in SPRINT attenders than controls (14 vs. >16 months, P=0.017). Conclusions: The SPRINT cohort tended to perform more procedures and achieved JAG certification earlier than controls. These data support the role for wider implementation of pre-clinical induction involving SBT.